2005
DOI: 10.1161/01.cir.0000157141.00778.ac
|View full text |Cite
|
Sign up to set email alerts
|

Plaque Instability Frequently Occurs Days or Weeks Before Occlusive Coronary Thrombosis

Abstract: Background-Acute ST-elevation myocardial infarction (STEMI) is caused by sudden occlusive coronary thrombosis, after plaque disruption; however, a considerable time interval between plaque disturbance and the onset of symptoms has been suggested. We therefore studied the age of intracoronary thrombi, aspirated during angioplasty in patients with acute STEMI. Methods and Results-Percutaneous intracoronary thrombectomy during angioplasty was performed in 211 consecutive STEMI patients within 6 hours after onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(87 citation statements)
references
References 27 publications
10
75
1
1
Order By: Relevance
“…Similar findings were published for great groups of cerebral stroke (CVA) [16]. Recent studies confirmed that more than 75% of AMI are a result of atheroma fissuring and/or rupture [37][38][39] and strong links connect timing of these events with high CRA (neutron activity).…”
Section: Discussionsupporting
confidence: 77%
“…Similar findings were published for great groups of cerebral stroke (CVA) [16]. Recent studies confirmed that more than 75% of AMI are a result of atheroma fissuring and/or rupture [37][38][39] and strong links connect timing of these events with high CRA (neutron activity).…”
Section: Discussionsupporting
confidence: 77%
“…Cholesterol crystals were not observed. Nuclear fragmentation was present in all but 1 thrombus, indicating thrombi were older than 1 day according to the criteria by Rittersma et al 18. Hematoxylin‐eosin staining of thrombi revealed areas of different age with fibrin networks of variable density and both intact leukocytes and nonintact leukocytes.…”
Section: Resultsmentioning
confidence: 84%
“…The results of histopathological evaluations of aspirated intracoronary thrombi obtained from STEMI patients have recently been presented [73][74][75][76][77] . Rittersma et al investigated 199 aspirated intracoronary thrombi obtained from STEMI patients within six hours of symptom onset and pathologically classified them into fresh thrombi (<1 day old) composed of layered patterns of fibrin and intact platelets, erythrocytes and granulocytes and older thrombi with lytic (1 to 5 days) or organized (>5 days) changes 73) .…”
Section: Pathological Analysis Of Aspirated Intracoronary Thrombimentioning
confidence: 99%
“…Rittersma et al investigated 199 aspirated intracoronary thrombi obtained from STEMI patients within six hours of symptom onset and pathologically classified them into fresh thrombi (<1 day old) composed of layered patterns of fibrin and intact platelets, erythrocytes and granulocytes and older thrombi with lytic (1 to 5 days) or organized (>5 days) changes 73) . In that study, 50% of the thrombi were days or weeks old.…”
Section: Pathological Analysis Of Aspirated Intracoronary Thrombimentioning
confidence: 99%